Biofluorescence as a survey tool for cryptic marine species. Issue 3 (19th February 2018) - De Brauwer, Maarten; Hobbs, Jean‐Paul A.; Ambo‐Rappe, Rohani; Jompa, Jamaluddin; Harvey, Euan S.; McIlwain, Jennifer L.
Abstract: As ecosystems come under increasing anthropogenic pressure, rare species face the highest risk of extinction. Paradoxically, data necessary to evaluate the conservation status of rare species are often lacking because of the challenges of detecting species with low abundance. One group of fishes subject to this undersampling bias are those with cryptic body patterns. Twenty‐one percent of cryptic fish species assessed for their extinction risk (International Union for Conservation of Nature [IUCN]) are data deficient. We developed a nondestructive method for surveying cryptically patterned marine fishes based on the presence of biofluorescence (underwater biofluorescence census, UBC). Blue LED torches were used to investigate how widespread biofluorescence was in cryptic reef fishes in the Coral Triangle region. The effectiveness of UBC to generate abundance data was tested on a data‐deficient pygmy seahorse species ( Hippocampus bargibanti ) and compared with data obtained from standard underwater visual census (UVC) surveys. We recorded 95 reef fish species displaying biofluorescence, 73 of which had not been previously described as biofluorescent. Of those fish with cryptic patterns, 87% were biofluorescent compared with 9% for noncryptic fishes. The probability of species displaying biofluorescence was 70.9 times greater for cryptic species than for noncryptic species. Almost twice the number of H. bargibanti was counted using the UBC compared with UVC. For 2 triplefin species ( Ucla xenogrammus, Enneapterygius tutuilae ), the abundance detected with UBC was triple that detected with UVC. The UBC method was effective at finding cryptic species that would otherwise be difficult to detect and thus will reduce interobserver variability inherent to UVC surveys. Biofluorescence is ubiquitous in cryptic fishes, making this method applicable across a wide range of species. Data collected using UBC could be used with multiple IUCN criteria to assess the extinction risk of cryptic species. Adopting this technique will enhance researchers' ability to survey cryptic species and facilitate management and conservation of cryptic marine species. Abstract : Article impact statement : Underwater biofluorescence census nondestructively collects data needed to assess conservation status of cryptic species. Abstract : La Bioluminiscencia como Herramienta para Censar Especies Marinas Crípticas Resumen: Conforme los ecosistemas están sometidos a la creciente presión antropogénica, las especies raras enfrentan el riesgo de extinción más alto. Paradójicamente, con frecuencia son pocos los datos necesarios para evaluar el estado de conservación de las especies raras debido a las dificultades existentes en la detección de especies con abundancias bajas. Un grupo de peces sujeto a este sesgo de poco muestreo es aquel conformado por peces con patrones corporales crípticos. El 21% de las especies de peces crípticos evaluados por riesgo de extinción (Unión Internacional para la Conservación de la Naturaleza [UICN]) carece de datos. Desarrollamos un método no‐destructivo para el censo de peces marinos con patrones crípticos basado en la presencia de la bioluminiscencia (censo submarino de bioluminiscencia, UBC en inglés). Se utilizaron antorchas de LEDs azules para investigar cuán diseminada estaba la bioluminiscencia en los peces crípticos de arrecife en la región del Triángulo de Coral. La efectividad del UBC para generar datos de abundancia se probó con una especie deficiente de datos, el caballito de mar pigmeo ( Hippocampus bargibanti ), y se comparó con los datos obtenidos a partir de censos submarinos visuales (UVC, en inglés) estándar. Registramos 95 especies de peces de arrecife que exhibieron bioluminiscencia, 73 de las cuales no habían sido descritos previamente como bioluminiscentes. De aquellos peces con patrones crípticos, el 87% fue bioluminiscente en comparación con el 9% de los peces no‐crípticos. La probabilidad de que una especie exhibiera bioluminiscencia fue 70.9 veces mayor para las especies crípticas que para las no‐crípticas. Se contó casi el doble del número de H. bargibanti con el uso del UBC en comparación con el UVC. Para dos especies ( Ucla xenogrammus, Enneapterygius tutuilae ) la abundancia detectada con el UBC fue triple que aquella detectada con el UVC. El método UBC fue efectivo para hallar especies crípticas que de otra forma serían difíciles de detectar y por lo tanto reduciría la variabilidad entre observadores inherente a los censos UVC. La bioluminiscencia es ubicua en peces crípticos, lo que hace que este método sea aplicable a lo largo de una amplia gama de especies. Los datos recolectados usando el UBC podrían usarse con múltiples criterios de la UICN para valorar el riesgo de extinción de las especies crípticas. Adoptar esta técnica mejorará la habilidad de los investigadores para censar especies crípticas y facilitar el manejo y la conservación de las especies crípticas marinas. 摘要: 生物荧光在调查隐秘海洋物种中的应用 随着人类对生态系统的影响与日俱增, 珍稀物种正面临极高的灭绝风险。矛盾的是, 由于探测低丰度物种的难度较大, 评估珍稀物种的濒危等级所必需的数据时常匮乏。其中有一大类身体含有隐秘图案的鱼类的评估, 就受到低样本量的抽样偏差影响。来自世界自然保护联盟 (IUCN) 的数据显示, 21%的这类鱼类因为数据缺乏而无法准确评估其灭绝风险。这里, 我们发展了一个基于生物荧光 (水下生物荧光调查, UBC) 的非损伤取样方法来调查有隐秘图案的海洋鱼类。我们用蓝光LED手电探究了珊瑚大三角地区这类岩礁鱼类中生物荧光的普遍性, 并用一个数据资料缺乏的倭海马 ( Hippocampus bargibanti) 检验了UBC法获取数据的效力, 同时与标准的水下视觉调查法 (UVC) 所得到的数据进行了比较。我们一共记录到95种有生物荧光的岩礁鱼类, 其中73种之前没有关于生物荧光的记载。在有隐秘图案的鱼中, 87%有生物荧光, 这在没有隐秘图案的鱼中仅有9%。隐秘种展现出生物荧光的概率是非隐秘种的70.9倍。例如, 用UBC法记录的巴氏豆丁海马 ( H. bargibanti) 的数量是用UVC法的近两倍。而在两种三鳍鱼 ( Ucla xenogrammus 和 Enneapterygius tutuilae) 研究中, 用UBC法检测到的丰度是UVC法的三倍。我们的研究表明, UBC法可有效用于寻找这些难以用其它方法探测到的隐秘物种, 因此可以减少UVC调查方法中出现的观察者之间的误差。由于在隐秘的鱼类物种普遍存在生物荧光, 使得这个方法可以大范围应用于许多物种。用UBC法收集的数据可以用于IUCN的多重标准, 来评估隐秘种的灭绝风险。同时, 采取这种技术可以提高研究者对隐秘种的调查能力, 并有利于隐秘的海洋物种的管理和保护。【翻译:胡怡思;审校:聂永刚】